2023
DOI: 10.1097/hc9.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Reengagement strategies for hepatitis C patients lost to follow-up: A randomized clinical trial

Abstract: Background and Aims: To achieve the World Health Organization’s goal of eliminating HCV by 2030, reengagement of lost to follow-up cases is mandatory. However, there is lack of evidence concerning the best strategy. Our study evaluated the effectiveness, efficiency, predictive factors, and costs of 2 different strategies. Methods: We identified patients positive for HCV antibodies without RNA requests from 2005 to 2018. Patients fulfilling trial criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The number of patients who could be relinked here (25 %) falls within the range observed in other ReLink projects, with 31 % [22] and a randomized clinical trial (25 %) [23], or is lower than reported for other projects (50 % to 74 %) [21,24]. The percentage of patients who finally received treatment (40 %) exceeds the reported overall DAA treatment rate (19 %) for six ReLink projects [22] and is similar to a ReLink project in Latin America, being one of the six [25], and a Spanish ReLink project (each 25 %) [21], and lower than compared to the French RECONVOCC study (40 %) [24].…”
Section: Discussionsupporting
confidence: 69%
“…The number of patients who could be relinked here (25 %) falls within the range observed in other ReLink projects, with 31 % [22] and a randomized clinical trial (25 %) [23], or is lower than reported for other projects (50 % to 74 %) [21,24]. The percentage of patients who finally received treatment (40 %) exceeds the reported overall DAA treatment rate (19 %) for six ReLink projects [22] and is similar to a ReLink project in Latin America, being one of the six [25], and a Spanish ReLink project (each 25 %) [21], and lower than compared to the French RECONVOCC study (40 %) [24].…”
Section: Discussionsupporting
confidence: 69%
“…Chronic hepatitis C, a chronic viral disease caused by hepatitis C virus (HCV) infection, is a major public health problem and a leading cause of chronic liver disease. [ 1 ] According to the World Health Organization, an estimated 71 million people worldwide are infected with HCV, and >350,000 people die of HCV-induced liver disease annually. [ 2 ] In China, there are approximately 10 million patients with HCV infection, accounting for >14% of the global HCV-infected population.…”
Section: Introductionmentioning
confidence: 99%